Strategy of Opening MyRepublic Wi-Fi Provider Area In Purwakarta District Using Moora Method - Defriani, Meriska; Resmi, Mochzen Gito; Alam, Syariful; Irmayanti, Dede (Jurnal Teknologi Informatika dan Komputer, 2025)
In today's digital era, the internet has become a basic need that is inseparable from the lives of modern society. Almost all aspects of human life now depend on internet connectivity, from communication, education, work, entertainment, to financial transactions. The development of digital technology and increasingly widespread internet penetration have changed the way people live, work, and learn. The trend of internet usage, especially in Indonesia, continues to experience significant growth from year to year. As the need for internet access in Indonesia increases, determining a strategic location is an important factor for service providers such as MyRepublic to expand Wi-Fi coverage. This study aims to assist the decision-making process using the Multi-Objective Optimization on The Basis of Ratio Analysis (MOORA) method. The study was conducted in Plered District, Purwakarta Regency, with five alternative locations: Citeko Village, Cadasmekar, Citalang, Batutumpang, and Liunggunung. Data were obtained through observation and interviews, with criteria including the number of houses, resident responses, competitors, administrative costs, and distance to the Optical Line Terminal (OLT). The results showed that Citalang Village had the highest preference value (Yi = 0.2735), followed by Batutumpang (Yi = 0.2356) and Cadasmekar (Yi = 0.2178). The MOORA method has proven effective in analyzing multi-criteria, providing optimal location recommendations based on data. In conclusion, this method can help companies make strategic decisions more focused and accurate.